2016
DOI: 10.1007/s12028-016-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Use in the Treatment of Super-Refractory Status Epilepticus is Associated with Hippocampal Changes on MRI

Abstract: Hippocampal signal changes were associated with isoflurane use in patients with RSE. They were also associated with number of seizure days prior to MRI and the use of multiple anesthetic agents. Similar changes have been seen as a result of RSE itself, and one cannot rule out the possibility these changes represent seizure-related effects. If isoflurane-related, these hippocampal signal changes may be the result of a direct neurotoxic effect of prolonged isoflurane use or failure of isoflurane to protect the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…It has been suggested that isoflurane may cause morphological cerebral MRI changes, especially in the thalamus, hippocampus, and cerebellum, because of proposed disturbances in brain metabolism in a dose-dependent and/or time-dependent manner [28,29]. On the other hand, similar peri-ictal MRI changes can also be caused by prolonged seizure activity itself [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that isoflurane may cause morphological cerebral MRI changes, especially in the thalamus, hippocampus, and cerebellum, because of proposed disturbances in brain metabolism in a dose-dependent and/or time-dependent manner [28,29]. On the other hand, similar peri-ictal MRI changes can also be caused by prolonged seizure activity itself [30].…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Cologne University Ethics Committee (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Because of the retrospective study design, written informed consent was waived.…”
Section: Patient Cohortmentioning
confidence: 99%
“…Additionally, clinicians should consider inhaled anesthetics such as isoflurane and desflurane in prolonged cases of SRSE [ 32 ]. However, hippocampal atrophy was reported with the use of inhaled anesthetics [ 33 ]. In this section, we discuss the most commonly used anesthetics for the treatment of RSE and SRSE ( Table 2 ).…”
Section: Treatment Of Rse and Srsementioning
confidence: 99%
“…• Inhalational anesthetics: Isoflurane and less commonly, desflurane, have been described for the treatment of SRSE. 55,56 There are several problems associated with the use of volatile anesthetics such as hypotension and frequent relapse of seizures upon termination of the anesthetic. There are also concerns of direct neurotoxicity with the use of high doses of isoflurane.…”
Section: Management Of Super-refractory Status Epilepticusmentioning
confidence: 99%